Knowledge received by hospital patients—a factor connected with the patient‐centred quality of nursing care. Issue 6 (1st April 2014) - Leino‐Kilpi, Helena; Gröndahl, Weronica; Pekonen, Arja; Katajisto, Jouko; Suhonen, Riitta; Valkeapää, Kirsi; Virtanen, Heli; Salanterä, Sanna
Abstract : The main purpose of this study was to evaluate and analyse the connection between the level of quality of nursing care and knowledge received by patients ( N  = 266, n  = 226), response rate was 85%. The data were collected using two structured instruments: one measuring the quality of nursing care experienced by patients (The Good Nursing Care Scale, GNCS) and one measuring the received knowledge of hospital patients (RKHP). The data were collected at one (out of five) Finnish university hospitals, in all medical wards during 5 weeks in 2009. A clear association between the level of the quality of nursing care and the level of received knowledge was found: on the total level of instruments, correlation was strong (r = 0.705). Support of empowerment (GNCS) had statistically significant strong correlation between biophysiological knowledge (RKHP), ( r  = 0.718), and experiential knowledge ( r  = 0.633), ( P  ≤ 0.01). Furthermore, there was a strong correlation between nursing activities and biophysiological knowledge ( r  = 0.637). Higher age, sufficient advance information and better self‐perceived health status were associated both with the level of the quality of nursing care and level of received knowledge. In the future, a special attention should be paid to the sufficient information for patients before their hospital stays.